Practice Improvement for Standardized Evaluation and Management of Acute Tracheitis in Mechanically Ventilated Children. Issue 1 (January 2021) - Ormsby, Jennifer; Conrad, Paula; Blumenthal, Jennifer; Carpenter, Jane; Jones, Sarah; Sandora, Thomas J.; Vaughan, Ana; Vincuilla, Julie; McAdam, Alexander J.; Fogg, Louis F.; Flett, Kelly; Kelly, Daniel P.
Abstract : Introduction: There is no consensus definition for ventilator-associated tracheitis and limited evidence to guide diagnosis and treatment. To improve acute tracheitis evaluation and management, this quality improvement project aimed to (1) improve the appropriateness of tracheal aspirate cultures while decreasing the number of unnecessary cultures by 20% and (2) decrease antibiotic use for acute tracheitis not consistent with local guidelines by 20% over 12 months among pediatric patients requiring mechanical ventilation. Methods: All patients admitted to the Medical Intensive Care Unit requiring mechanical ventilation via an artificial airway were included. Tracheal aspirate sampling criteria, technique, and minimum intervals were standardized. Primary outcome measures were the number of tracheal aspirate cultures obtained per 100 ETT/tracheostomy days and ventilator-associated antibiotic days per 100 ETT/tracheostomy days. Improvement cycles included: Implementation of tracheal aspirate sampling criteria, sampling technique standardization, limiting repeat cultures to >72-hour intervals, and standardizing empiric antibiotic therapy. Results: Tracheal aspirate culture rate decreased from 10.70 to 7.10 cultures per 100 ETT/tracheostomy days ( P < 0.001). Cultures meeting sampling criteria increased from 28% to 80%. Ventilator-associated antibiotic use decreased from 24.88 to 7.30 ventilator-associated antibiotic days per 100 ETT/tracheostomy days. There were no associated increases in ventilator-associated events or days of mechanical ventilation. Conclusions: Implementation of standardized criteria for tracheal aspirate sampling, improved tracheal aspirate sampling technique, limiting repeat tracheal aspirate cultures, and utilizing standardized antibiotic treatment guidelines safely decreased resource utilization and antibiotic use among critically ill children requiring mechanical ventilation.